STILISASI MOTIF ORNAMEN PADA LIMBAH DAUR ULANG UNTUK PRODUK KREATIF - Syahbani, Reza; Tantri, Karlina; Panisia, Terra (Faculty of Teacher Training and Education, 2025)
This study explores the potential for stylization of traditional ornament motifs applied to recycled waste to create value-added creative products. The main objective of the research is to develop innovative methods of processing waste into raw materials of creative products through the application of distilled ornament motifs. Methods used include literature studies of traditional ornament motifs, stylization technique experiments, and application trials on different types of recycled waste. The results of the study showed that stylization of ornament motifs can increase the aesthetic value and uniqueness of recycled waste products. The developed stylization techniques are successfully applied to plastic, textile, and paper waste, resulting in product prototypes such as accessories, decorative elements, and packaging. This research contributes to the development of a recycling-based creative industry and the preservation of cultural heritage through the reinterpretation of traditional ornament motifs.